(untitled) (Research, Society and Development, 2021)
The woman farmer participates in the social, economic and political spheres in the family agricultural context, going beyond the care of the home and contributing to the family’s livelihood. Through empirical research using a semi-structured questionnaire, this study aimed to understand the dynamics and participation of cooperative women farmers of the Potiguar Beekeepers Cooperative and Sustainable Rural Development - COOPAPI in the locality of Sítio Córrego, Municipality of Apodi, State of Rio Grande North, in the context of family farming, and to verify the group’s acceptance of oilseed cultivation, which is growing in the region. Farmers work actively and effectively in the creation of small animals, plant care, fruit marketing and cake production. In addition to caring for the home, they carry out multiple activities to ensure the complement of family livelihood, whether in the domestic, agricultural or commercial sectors. Such tasks are often unpaid, still seen only as “help”, which contributes to the invisibility and devaluation of female agricultural work.